Stages in the psychological resolution of schizophrenia - Steggles, Gillian R. M. (Frontiers in Psychology, 2015)
From the work of Dr. Michael Robbins in Massachusetts, USA, it is known that nine schizophrenic patients out of a series of 18, and a further schizophrenic patient, treated by him achieved positive outcomes using psychoanalytic methodology. Four of these had strikingly successful outcomes, for example completing their treatment without a need for further medication, and also becoming happily married or graduating at university. This paper aims to illustrate the stages identified by him through which this can be accomplished. Dr. Robbins’ Stages of Psychological Therapy of Schizophrenia are compared with Dr. Steggles’ detailed case study of a patient’s recovery from schizoaffective disorder. These two data sources are juxtaposed and compared. Dr. Robbins’ therapeutic stages are found to parallel exactly Dr. Steggles’ findings from her case study, which she summarized as her psychodynamic pentapointed cognitive construct (PPCC) model of her schizoaffective patient’s experience. Psychological therapy of schizophrenia is still in its early stages of development. However, Dr. Robbins’ psychoanalytic psychotherapeutic technique has given rise to positive outcomes in 10 of the 19 patients he treated, that is, his series of 18 patients together with a further patient; these 19 patients he gave full psychological treatment, i.e., usually four sessions per week. The Stages he identifies in his therapeutic process match perfectly the stages Dr. Steggles identified in her own patient’s healing mind. Not all schizophrenic patients are likely to be able to benefit from this psychological therapy. Females seem to be better able than males to respond to the treatment, and motivation is necessary for a successful outcome. It is not known how to identify precisely those patients who will be successful. But those patients who do benefit may counterbalance by their economic activity the healthcare costs of those who do not recover, as well as achieving benefit from their human suffering. Many of the other groups of patients suffering from schizophrenia can be helped by engaging with a clinician for social skills or family therapy, and where appropriate this should always be done.